2015
DOI: 10.1002/ajmg.a.37355
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalies associated with trisomy 18 or trisomy 13: A registry‐based study in 16 european countries, 2000–2011

Abstract: The aim of this study was to examine the prevalence of trisomies 18 and 13 in Europe and the prevalence of associated anomalies. Twenty-five population-based registries in 16 European countries provided data from 2000-2011. Cases included live births, fetal deaths (20+ weeks' gestation), and terminations of pregnancy for fetal anomaly (TOPFAs). The prevalence of associated anomalies was reported in live births. The prevalence of trisomy 18 and trisomy 13 were 4.8 (95%CI: 4.7-5.0) and 1.9 (95%CI: 1.8-2.0) per 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 21 publications
3
83
1
3
Order By: Relevance
“…The prevalence of coexisting anomalies in this study was consistent with other published reports. (29–31, 35) Although most studies on surgical intervention for infants with T13 or T18 have focused on congenital heart disease, (5, 24) we found that the most common condition associated with early neonatal surgery was tracheoesophageal fistula. Surgical decision-making for non-cardiac conditions is an important area for further research.…”
Section: Discussionmentioning
confidence: 80%
“…The prevalence of coexisting anomalies in this study was consistent with other published reports. (29–31, 35) Although most studies on surgical intervention for infants with T13 or T18 have focused on congenital heart disease, (5, 24) we found that the most common condition associated with early neonatal surgery was tracheoesophageal fistula. Surgical decision-making for non-cardiac conditions is an important area for further research.…”
Section: Discussionmentioning
confidence: 80%
“…All other typical features can appear in both disorders. Trisomy 18 often has sonographic features similar to Pena‐Shokeir syndrome, such as polyhydramnios, intrauterine growth restriction, and abnormal postures of the extremities secondary to skeletal muscle hypoplasia as well as diminished fetal activity . Normal fetal karyotype should exclude trisomy 18.…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy 18 often has sonographic features similar to Pena-Shokeir syndrome, such as polyhydramnios, intrauterine growth restriction, and abnormal postures of the extremities secondary to skeletal muscle hypoplasia as well as diminished fetal activity. 13 Normal fetal karyotype should exclude trisomy 18. Neu-Laxova syndrome may show polyhydramnios, growth restriction, skeletal anomalies, microcephaly, prominent eyes, retrognathism, and hypomobility with flexion deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Nondisjunction errors occur with increased frequency in advanced maternal age, which is a major risk factor for the development of trisomy abnormalities (Savva, Walker, & Morris, ). A European study of 3,624 trisomy 18 cases in 21 countries indicated that approximately 3% had neural tube defects (NTDs) and 6% had omphalocele (OMP; Springett et al, ). Demographically, 66–80% of trisomy 18 syndromes are reported in female fetuses (Parker et al, ; Rosa et al, ).…”
Section: Introductionmentioning
confidence: 99%